Pengaruh Harga Dan Celebrity Endorser Terhadap Minat Beli Shampo Clear (Studi Kasus Pada Mahasiswa Universitas Sari Mutiara Indonesia) - Purba, Roberto Roy; Wati, Feni (Metta : Jurnal Ilmu Multidisiplin, 2021)
Advertising through celebrity endorsers is currently in great demand to introduce and promote products to the public. The use ofadvertisements is celebrity endorser considered effective to increase product sales, this is because the development of very fast information flow is supported by the existence of technology that makes consumers able to absorb information and knowledge about a product quickly. Likewise with pricing strategies that can affect consumer buying interest. This study aims to determine the effect of price on interest in buying shampoo clear to the students of the Sari Mutiara Indonesia University, celebrity endorser on interest in buying shampoo clear to the students of the Sari Mutiara Indonesia University and celebrity endorser on interest in buying shampoo clear to the students of the Sari Mutiara Indonesia University. This research was conducted using a quantitative descriptive method by distributing questionnaires to 100 student respondents at the Sari Mutiara Indonesia University which were analyzed by multiple linear regression, the sampling technique was using Non-Probability Sampling.The results of this study indicate that the price variable (X1) has a significant positive effect on the buying interest variable (Y) while thevariable celebrity endorser (X2) has a significant positive effect on the buying interest variable (Y). It can be concluded that the influence of each variable simultaneously can be seen that Fhitung(117.184) >Ftable (3.09) or sig. of 0.000 < 0.05. The data were statistically processed using SPSS 25 program tools.